Carbon credit card services and the impact potential on Co2 emissions in the Eu - climate crisis analysis and the relevance of sustainable finance - Kreß, Teresa (2021)
This section analyzes how climate change awareness and political initiatives evolved over the past decades and what role Carbon Credit Card Services (CCCS) play among current decarbonizing initiatives. To answer these questions, factors causing climate change and resulting consequences from an ecological, societal and economic perspective were identified. The study shows the need for climate change mitigation initiatives on three layers: governments, corporations and consumers. The results reveal that among the corporate side, the financial sector plays a significant role in the transition to carbon-neutrality. The specific impact of Carbon Credit Card Services will be further investigated within a thought experiment in the following sections.